The Drosophila homolog of Onecut homeodomain proteins is a neural-specific transcriptional activator with a potential role in regulating neural differentiation. - Nguyen, D.N.T.; Rohrbaugh, M.; Lai, Z.C. (Mechanisms of Development, 2000)
We report here the characterization of the Drosophila homolog of the onecut homeobox gene, which encodes a protein product with one cut domain and one homeodomain. We present evidence that D-Onecut can bind to similar DNA sequences with high specificity and affinity as other Onecut proteins through the highly conserved cut domain and homeodomain. Interestingly, the cut domain alone can mediate DNA-binding, but the homeodomain cannot. However, depending upon the promoter context, we observed cooperative interactions between the two domains to confer high DNA-binding affinity and specificity. D-Onecut appears to be a moderate transcriptional activator and functions as a nuclear protein in neuronal tissues of both the CNS and PNS during development and in the adult. In the eye, D-Onecut expression is independent of glass, a transcriptional regulator of R cell differentiation. Taken together, our results suggest a role for D-Onecut in the regulation of some aspects of neural differentiation or maintenance. In support of this notion, overexpression of a putative dominant negative form of D-Onecut during eye development does not affect early cell fate specification, but severely affects photoreceptor differentiation.